Peer Review Practices for Evaluating Biomedical Research Grants: A Scientific Statement From the American Heart Association. Issue 4 (4th August 2017) - Liaw, Lucy; Freedman, Jane E.; Becker, Lance B.; Mehta, Nehal N.; Liscum, Laura
Abstract : The biomedical research enterprise depends on the fair and objective peer review of research grants, leading to the distribution of resources through efficient and robust competitive methods. In the United States, federal funding agencies and foundations collectively distribute billions of dollars annually to support biomedical research. For the American Heart Association, a Peer Review Subcommittee is charged with establishing the highest standards for peer review. This scientific statement reviews the current literature on peer review practices, describes the current American Heart Association peer review process and those of other agencies, analyzes the strengths and weaknesses of American Heart Association peer review practices, and recommends best practices for the future.